Doctorate education: a practical guide - Baporikar, Neeta (New Delhi : Viva Books Pvt.Ltd., 2010)
Doing a Ph.D. implies a double quest. On the one hand, it is an academic exercise with theories and data in search of descriptions or explainations. On the other, it is a search for a personal path within the academic community. It requires a combination of academic skills, intuition, hard effort and confidence. Written in an informal style, this book helps candidates to understand the fundamentals and challenges in pursuing a research degree, and to adapt to the entrepreneurial learning practices in a research career. This book would provide practical guidelines on how to go about, not only doing research and completing doctorate, but also enjoying it throughout the journey. It can be used by all those who are thinking of research and those who are in the process of doing their doctorate, whatever the stage they are in.
Include bibliographical reference and appendix.
Keywords: Academic degrees